2008
DOI: 10.2174/157488708783330512
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy with Gemcitabine in Advanced Biliary Tract Carcinoma

Abstract: Gemcitabine is an effective drug in advanced biliary tract carcinoma with a low toxicity profile. It should be considered as the standard treatment for unresectable or metastatic disease while awaiting phase III results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…The results presented here suggest that Gem-based combination chemotherapy induced more toxicity compared with Gem alone or non-Gem-based chemotherapy. However, all severe hematological toxicities (grade 3 or 4) are infrequent and reversible, and these results are consistent with a previous study [24] . Several limitations of our meta-analysis should be mentioned.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results presented here suggest that Gem-based combination chemotherapy induced more toxicity compared with Gem alone or non-Gem-based chemotherapy. However, all severe hematological toxicities (grade 3 or 4) are infrequent and reversible, and these results are consistent with a previous study [24] . Several limitations of our meta-analysis should be mentioned.…”
Section: Discussionsupporting
confidence: 93%
“…However, the analysis involved studies that evaluated Gem plus platinum chemotherapy; thus, new treatments, such as Gem plus S-1, were not included. A review published by Serrano et al [24] also suggested that Gem alone or in combination with other agents showed a better response rate that correlated with the time to progression. Additionally, regimens that contained two drugs induced higher response rates compared with single agent treatments.…”
Section: Discussionmentioning
confidence: 97%
“…GEM is the standard chemotherapeutic regimen for advanced pancreatic cancer and advanced biliary tract cancer 18,19 . GEM (2′, 2′‐difluorodeoxycytidine) is a nucleoside analog that is phosphorylated to produce the active metabolites difluorodeoxycytidine diphosphate and triphosphate 20 . These metabolites exert their cytotoxic effects primarily by inhibiting DNA synthesis and inducing apoptosis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites exert their cytotoxic effects primarily by inhibiting DNA synthesis and inducing apoptosis 21 . Severe hematological or non‐hematological toxicities associated with GEM are reported to be infrequent and reversible 20 . Based on its promising anti‐tumor effect and safety profile, we selected GEM as the basis for a DES for malignant biliary obstruction in pancreaticobiliary cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4 In single-agent therapy, GEM demonstrated moderate efficacy (17.5% partial response rate) with manageable toxicity in patients with BTC. 5 Recently, results from randomized phase III studies (ABC-02, have demonstrated that patients receiving a GEM-cisplatin combination had a significantly longer progression-free survival and overall survival (11.7 compared with 8.1 months; HR 0.64 [95% CI 0.52 to 0.80]; log rank p < 0.001) 6 than GEM single agent with an acceptable toxicity. 6,7 Despite 1 these findings, the effect of chemotherapy on survival or ORR is still not sufficient, and the development of additional regimens is required.…”
Section: Introductionmentioning
confidence: 99%